Staphylococcus aureus sporotrichoid lymphangitis without bacteremia in a transplant recipient. Issue 1 (13th January 2015) - Rotemberg, V.; Valins, W.; Husan, S.; Grossman, M.
Abstract Pyogenic sporotrichoid infections are rare. There are only 4 reports in the literature of Staphylococcus aureus presenting as sporotrichoid lymphangitis (also known as lymphocutaneous syndrome or nodular lymphangitis). We report the first case, to our knowledge, of S. aureus sporotrichoid infection without bacteremia in an immunocompromised organ transplant recipient.